Pediatric COVID-19: Report From Indonesian Pediatric Society Data Registry - Pudjiadi, Antonius H.; Putri, Nina Dwi; Sjakti, Hikari Ambara; Yanuarso, Piprim Basarah; Gunardi, Hartono; Roeslani, Rosalina Dewi; Pasaribu, Ade Djanwardi; Nurmalia, Lies Dewi; Sambo, Catharine Mayung; Ugrasena, I Dewa Gede; Soeroso, Santoso; Firman, Armijn; et al. (Frontiers in Pediatrics, 2021)
Background Indonesia still has a high number of COVID-19 cases and mortalities relative to not only the Asia Pacific region but the world. Children have been thought to be less affected by the virus compared to adults. Most of the public data reported combined data between adults and children. The Indonesian Pediatric Society (IPS) was involved in the COVID-19 response, especially in the area of child health. One of IPS’s activities is collecting data registries from each of their chapters to provide a better understanding of COVID-19 in children. Objective To share the data of suspected and confirmed COVID-19 cases in children from IPS’s COVID-19 data registry. Method This is a retrospective study using data from the IPS’s COVID-19 registry. We collected the data of COVID-19 in children during March to December 2020 from each of the IPS chapters. We analyzed the prevalence, case fatality rate (CFR), age groups, diagnosis, and comorbidities of the children diagnosed with COVID-19. Result As of December 21, 2020, there were 35,506 suspected cases of children with COVID-19. In total, there were 522 deaths, with a case fatality ratio (CFR) of 1.4. There were 37,706 confirmed cases with 175 fatalities (CFR 0.46). The highest mortality in confirmed COVID-19 cases was from children ages 10–18 years old (42 out of 159 cases: 26%). The most common comorbidity and diagnosis found were malignancy (17.3%) and respiratory failure (54.5%). Conclusion The CFR of confirmed COVID-19 cases in children in Indonesia is high and should be a major public concern.